HIDROPONIK SEBAGAI BENTUK PEMANFAATAN LAHAN SEMPIT UNTUK PENINGKATAN PENDAPATAN RUMAH TANGGA DI NAGARI SUNGAI KAMUYANG - Devi Yulia Rahmi; Ranny Fitriana Faisal; Agestayani Agestayani; Susiana Susiana; Winny Alna Marlina; Fatma Poni Mardiah; Erizal Erizal; Faisal Ali Ahmad; Musbatiq Srivani (Jurnal Hilirisasi IPTEKS, 2020)
Narrow land is a problem for conventional agriculture to grow crops Management of small area can be overcome with a hydroponic system that utilizes technology in farming. Small area owned by households can be maximized for agriculture. However, household stigma is still fixed on conventional agriculture by managing large tracts of land. This stigma must then be changed by giving literacy to households about farming using the hydroponic method. Based on this understanding, Department of Management Campus II Universitas Andalas held socialization and training with the theme "Utilizing Small Area to Increase Household Incomes, Through Cultivation Using the Hydroponic System". The primary purpose of this activity is to provide knowledge through training to residents of the Nagari Sungai Kamuyang on the use of hydroponic systems. Another goal is to provide interest in business opportunities that can be generated from farming using the hydroponic system, exploring the creativity of citizens in the use of narrow land, and producing clean and healthy plants. The dedication method uses lectures, hands-on practice, and discussion with speakers. Community service activities are carried out at the Kamuyang Nagari guardian's office. In organizing this training, the participants are equipped with necessary knowledge related to hydroponics, and then directly practice farming with the hydroponic wick system. The community expects activities like this to continue to be carried out in the framework of better community empowerment.